Minimally invasive vs. conventional mitral valve surgery: a meta-analysis of randomised controlled trials - Amin, Aamir; Kumar, Rajanikant; Mokhtassi, Shiva Seyed; Alassiri, Abdullah K.; Odaman, Agatha; Khan, Muhammad Ahmad Raza; Lakshmana, Shashi; Din, Zahir Ud; Acharya, Pawan; Cheema, Huzaifa Ahmad; Nashwan, Abdulqadir J.; Khan, Arsalan Ali; et al. (Frontiers in Cardiovascular Medicine, 2024)
The evidence underlying the efficacy and safety of minimally invasive mitral valve surgery (MIMVS) is inconclusive. We conducted a meta-analysis to evaluate whether MIMVS improves clinical outcomes compared with conventional sternotomy.We searched MEDLINE (via PubMed), Embase, the Cochrane Library, and ClinicalTrials.gov from inception to January 2024 for all randomised controlled trials (RCTs), comparing MIMVS with conventional mitral valve surgery. RevMan 5.4 was used to analyse the data with risk ratio (RR) and mean difference (MD) as the effect measures.Results: Eight studies reporting data on 7 RCTs were included in our review. There was no significant difference in all-cause mortality, the number of patients requiring blood product transfusion, and the change from baseline in the SF-36 physical function scores between the MIMVS and conventional sternotomy groups. MIMVS reduced the length of hospital stay (MD -2.02 days, 95% CI: -3.66, -0.39) but did not affect the length of ICU stay, re-operation for bleeding, and the incidence of renal injury, wound infection, neurological events, and postoperative moderate or severe mitral regurgitation. MIMVS was associated with a trend toward lower postoperative pain scores (MD -1.06; 95% CI: -3.96 to 0.75).Conclusions: MIMVS reduced the number of days spent in the hospital and showed a trend toward lower postoperative pain scores, but it did not decrease the risk of allcause mortality or the number of patients needing blood product transfusions. Further large-scale RCTs are required to inform definitive conclusions, particularly with regard to quality-of-life outcomes investigating functional recovery.